2006
DOI: 10.1111/j.1443-1661.2007.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Polypoid Colonic Hamartomatous Inverted Polyp

Abstract: We herein present a unique polyp diagnosed as polypoid colonic hamartomatous inverted polyp. Colonoscopic examination revealed a clover-like submucosal tumor about 30 mm in size with a long stalk at the mid-transverse colon. The polyp consisted of elongated crypts with cystic dilatation located in the submucosal layer. To the best of our knowledge, there have been no previous reports of the same type of pedunculated colonic polyp, similar in appearance to inflammatory myoglandular polyps but covered with a lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Tanaka et al [ 8 ] reported a polypoid colonic hamartomatous inverted polyp. Hamartomatous inverted polyps are benign masses formed by an inverted or downward growth of mucosal glands through the muscularis mucosa into the submucosa, occurring in the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al [ 8 ] reported a polypoid colonic hamartomatous inverted polyp. Hamartomatous inverted polyps are benign masses formed by an inverted or downward growth of mucosal glands through the muscularis mucosa into the submucosa, occurring in the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…The first report described three cases of this polyp in the rectum; however, almost all cases subsequently reported have been of the stomach. Apart from the first report, only one case of this polyp in the colorectum has been reported in English to date . We have shown the fifth case of hamartomatous inverted polyp in the colorectum along with its immunohistochemical characteristics.…”
mentioning
confidence: 56%
“…Apart from the first report, only one case of this polyp in the colorectum has been reported in English to date. 2 We have shown the fifth case of hamartomatous inverted polyp in the colorectum along with its immunohistochemical characteristics. Next, we provide a discussion about its differential diagnoses, particularly from Peutz-Jeghers-type hamartomatous polyps and inverted hyperplastic polyps.…”
Section: To the Editormentioning
confidence: 85%
“…Polypoid colonic hamartomatous inverted polyp is a benign lesion of the rectum, due to an inverted or downward growth of mucosal glands through the muscularis mucosa into the submucosa[46]. Microscopically, a circumscribed group of ectopic distorted, slightly atypical mucus glands are present in the submucosa, pushing the mucosa up to form a polypoid mass[50]. Epithelial eosinophilia and lymphoid aggregates are not a feature of this lesion.…”
Section: Discussionmentioning
confidence: 99%